PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 1 LUBUK SIKAPING - Yasnel, Satriafani; Delsi K, Delsi K; Haryono, Yulia (STKIP PGRI Sumbar, 2014)
ABSTRACTThe background of this research by understanding the concept of mathematical student in learning mathematics is still low and the lack of cooperation among students in understanding the material provided. The purpose of this study was determine whether students understanding of mathematical concept with application of cooperative learning student achievement team division (STAD) better than student understanding of mathematical concept with conventional learning. This type research is experimentalÂ conducted with the subject randomized study design.Â Instrument used in the study is the final test in the form of essays. With the realibity test 0,826. Based on the analysis of data obtained t, 4,18 â¥ 1,7127 then reject H0 with H1 received. It can be concluded that the students understanding of matematics concepts with the implementation of cooperative learning student team achievement division (STAD) better than students understanding of mathematical concepts with convensional learning on students class IX SMPN 1 Lubuk Sikaping